2017
DOI: 10.1055/s-0043-117955
|View full text |Cite
|
Sign up to set email alerts
|

Side-by-side partially covered self-expandable metal stent placement for malignant hilar biliary obstruction

Abstract: Background and study aims  This study investigated the feasibility of side-by-side (SBS) partially covered self-expandable metal stent (PCSEMS) placement for unresectable malignant hilar biliary obstruction (MHBO). Patients and methods  We retrospectively analyzed 33 patients from a single center who underwent endoscopic biliary drainage for unresectable MHBO from July 2013 to June 2015. In all patients with bilateral obstruction during complete bilateral intrahepatic cholangiograms, we performed endoscopic SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…The Asia‐Pacific Working Group for hepatobiliary cancers have reported that optimal palliative stenting for hilar cholangiocarcinoma requires draining ≥50% or more of the liver volume . Therefore, bilateral SEMS can be deployed under such circumstances using side‐by‐side (SBS) or stent‐in‐stent (SIS) techniques . The incidence of complications seems higher when stents are deployed using SBS technique .…”
Section: Introductionmentioning
confidence: 99%
“…The Asia‐Pacific Working Group for hepatobiliary cancers have reported that optimal palliative stenting for hilar cholangiocarcinoma requires draining ≥50% or more of the liver volume . Therefore, bilateral SEMS can be deployed under such circumstances using side‐by‐side (SBS) or stent‐in‐stent (SIS) techniques . The incidence of complications seems higher when stents are deployed using SBS technique .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recently, metal stents with strong expansive force along the short axis and covered stents have been used when performing the SBS technique. 14,15 However, in such cases, attention must be paid to possible cholecystitis following stent placement. In cases where cholecystitis progresses to fatality; gall bladder drainage should be considered as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Quality assessment of the observational studies was done by NIH quality assessment tool for Before-After (Pre-Post) Studies With No Control Group. Nine studies [24, 25 ,28-31, 34, 35, 38] had good quality and seven studies [23,26,27,32,36,37,39] had fair quality (▶ Table 3).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%